Pengembangan Aplikasi Perangkat Bergerak Identifikasi Penyakit Daun Jeruk Berbasis Android dengan Memanfaatkan Vize AI - Sisco Jupiyandi; Agi Putra Kharisma; Anang Triwiratno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Citrus plants are one of the important plants that get a special consideration by the Indonesian government. Based on research conducted by the Indonesian Ministry of Agriculture, citrus plants have rapid experienced development every year both in terms of the area of agricultural, the amount of production, and the increasing number of market demands. Even though the production of citrus plants continues to increase, in reality the citrus farmers have many obstacles in the field, one of which is the knowledge of diseases that exist in citrus plants, thereby reducing the productivity of the citrus fruit itself. Vize AI is a web service that provides an API for image recognition that can be trained to recognize and classify any kinds of images including a custom image. The author takes advantage of the opportunity to develop mobile-based applications with Android OS that can identify diseases from image of citrus leaves into 3 diseases, namely Downy Mildew, Cendawan Jelaga, and Citrus Vein Phloem Degeneration (CVPD) by using Vize AI. Applications that have been made by the author have some features that meet the user's need and implemented in Java programming language. After accuracy test is done, the results of the accuracy of this application in detecting citrus leaf's disease is highly accurate result with a percentage of 100% and accuracy of calculation of severity has an average accuracy of 65%. But these results still depend on the type of image quality itself.